JURIDICAL ANALYSIS OF DIPLOMA RETENTION AGREEMENT AS A CONDITION OF WORKING IN THE COMPANY - Sulistiani; Astuti, Mirsa; Pohan, Masitah (Pena Cendekia Insani, 2026)
The practice of companies withholding diplomas as a condition of employment is an employment law issue that reflects the unequal position between employers and workers and the weak protection of workers' rights. Although this practice is not explicitly regulated in employment law, it has the potential to go against the principles of freedom of contract, fair employment relations, and human rights. This study aims to analyze the form of legal protection for workers, and the government's responsibility in preventing and combating this practice. Through normative legal research, it was concluded that the detention of diplomas could violate the constitutional rights of workers, potentially making the agreement invalid. Legal protection can be provided in a preventive and repressive manner, based on national law and international human rights instruments. The government's responsibility is strengthened through supervision, mediation, and the issuance of the Circular Letter of the Minister of Manpower No. M/5/HK.04.00/V/2025. Nevertheless, stronger laws and regulations are needed to ensure legal certainty and the effectiveness of legal protection for employees